Design of an efficient energy harvester from ambient vibration - Rahman, Tasfia; Rahman, Syedur; Onna, Shawzia Dewan (BRAC University, 2012)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2012.